PO139 Integrated safety analysis; cladribine in multiple sclerosis (ms). (1st December 2017) - Cook, Stuart; Leist, Thomas; Comi, Giancarlo; Montalban, Xavier; Sylvester, Elke; Hicking, Christine; Dangond, Fernando
Abstract : Background: Efficacy and safety of cladribine tablets (CT) has been investigated in patients with early MS and relapsing MS (RMS). Objective: Report the AE profile from integrated safety data for CT3.5 mg/kg (CT3.5) monotherapy. Methods: The monotherapy oral CT3.5 cohort comprised 923 patients (3432.65 patient years [PY] exposure); 641 patients received placebo (2025.97 PY). Results: Mean study period for CT3.5 was 194 weeks; placebo 165 weeks. Adj-AE per 100 PY rates for CT3.5 and placebo respectively: treatment emergent AEs, 103.3 and 94.3; serious AEs, 4.0 and 3.6; serious AEs leading to death, 0.26 and 0.25. For events expected with CT treatment, adj-AE per 100 PY for lymphopenia were 7.94 (CT3.5) and 1.06 (placebo), and for system organ class (SOC) infection and infestations, 24.93 (CT3.5) and 27.05 (placebo); herpes zoster, 0.83 (CT3.5) and 0.20 (placebo). Adj-AE per 100 PY for SOC neoplasms, benign, malignant and unspecified were 1.14 and 1.01, for CT3.5 and placebo, respectively. Conclusions: The AE profile for CT3.5 monotherapy has been well-characterised. Lymphopenia was expected from cladribine tablets' mode of action; herpes zoster was reported more frequently in patients experiencing Grade 3/4 lymphopenia; no clustering of types of malignancy, and no malignancies commonly associated with immunosuppression were observed.